2002
DOI: 10.1099/00221287-148-6-1725
|View full text |Cite
|
Sign up to set email alerts
|

A third fatty acid Δ9-desaturase from Mortierella alpina with a different substrate specificity to ole1p and ole2p The EMBL accession number for the sequence reported in this paper is AJ278339.

Abstract: A third gene (∆9-3) encoding a fatty acid ∆9-desaturase was isolated from the oil-producing fungus Mortierella alpina. The predicted protein of 512 aa shared 53 % sequence identity with the two fatty acid ∆9-desaturases, ole1p and ole2p, already described in this organism and contained three histidine boxes, four putative transmembrane domains and a C-terminal cytochrome b 5 fusion that are typical of most fungal membrane-bound fatty acid desaturases. hexacosenoic acid ; ∆9-3, gene encoding fatty acid ∆9-desat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…D5 desaturase activity on VLCSFAs was demonstrated for ADS proteins from L. alba and A. leveillei (Cahoon et al, 2000;Sayanova et al, 2007). A related desaturase from the fungus Mortierella alpina has also been reported to catalyze synthesis of 26:1 (MacKenzie et al, 2002). Positional diversity of double-bond insertion catalyzed by this class of closely related proteins offers a unique opportunity to explore the mechanisms controlling regiospecificity of membrane-bound fatty acid desaturases.…”
Section: Discussionmentioning
confidence: 99%
“…D5 desaturase activity on VLCSFAs was demonstrated for ADS proteins from L. alba and A. leveillei (Cahoon et al, 2000;Sayanova et al, 2007). A related desaturase from the fungus Mortierella alpina has also been reported to catalyze synthesis of 26:1 (MacKenzie et al, 2002). Positional diversity of double-bond insertion catalyzed by this class of closely related proteins offers a unique opportunity to explore the mechanisms controlling regiospecificity of membrane-bound fatty acid desaturases.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] These genes have been extensively studied and it was found that addition of UFAs to the growth medium suppressed the expression of OLE1 gene in some yeasts, but not in others. 5,11) Furthermore, in S. cerevisiae, low-temperature stress was found to affect expression of OLE1 gene.…”
mentioning
confidence: 99%
“…Many genes for D9 fatty acid desaturases and D12 fatty acid desaturases have been cloned from fungi and well characterized (Stukey et al 1990;Huang et al 1999;Laoteng et al 1999;Passorn et al 1999;Wongwathanarat et al 1999;Calvo et al 2001;Kajiwara 2002;MacKenzie et al 2002;Watanabe et al 2004), and several of these genes are reported to be induced by low-temperature stress Calvo et al 2001;Nakagawa et al 2002;Watanabe et al 2004). Disruption of the odeA gene of the ascomycetous fungus Aspergillus nidulans, which encodes a D12 fatty acid desaturase, was also shown to influence the development of conidia and ascospores (Calvo et al 2001).…”
Section: Introductionmentioning
confidence: 96%